2023
DOI: 10.1177/0271678x231156982
|View full text |Cite
|
Sign up to set email alerts
|

A SPECT-based method for dynamic imaging of the glymphatic system in rats

Abstract: The glymphatic system is a brain-wide waste drainage system that promotes cerebrospinal fluid circulation through the brain to remove waste metabolites. Currently, the most common methods for assessing glymphatic function are ex vivo fluorescence microscopy of brain slices, macroscopic cortical imaging, and MRI. While all these methods have been crucial for expanding our understanding of the glymphatic system, new techniques are required to overcome their specific drawbacks. Here, we evaluate SPECT/CT imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 79 publications
1
23
0
Order By: Relevance
“…However, radiotracers may be used for dynamic scans that are three to four times longer than their half-life. Moreover, a recent study suggested the useful role of radiotracers for in vivo imaging of glymphatic function 47 . We recently introduced another method to assess CSF-to-blood clearance capacity 13 , incorporating an intrathecal injection of a CSF tracer (e.g., gadobutrol), followed by repeated plasma samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, radiotracers may be used for dynamic scans that are three to four times longer than their half-life. Moreover, a recent study suggested the useful role of radiotracers for in vivo imaging of glymphatic function 47 . We recently introduced another method to assess CSF-to-blood clearance capacity 13 , incorporating an intrathecal injection of a CSF tracer (e.g., gadobutrol), followed by repeated plasma samples.…”
Section: Discussionmentioning
confidence: 99%
“…This makes developments in noninvasive whole brain imaging technologies and computational analysis of fluid dynamics even more important. While the current most common methods for the assessment of glymphatic function are ex vivo fluorescence microscopy of brain slices and macroscopic cortical imaging with invasive tracer infusion, new techniques like noninvasive MR imaging are required to overcome these specific drawbacks (for a detailed review of current innovations in MR and SPECT imaging [80,81]). Using these techniques, future clinical trials will show whether maintaining vascular structure and function and improvement of glymphatic flow will prevent or delay the onset Alzheimer's disease and Cerebral Amyloid Angiopathy.…”
Section: Discussionmentioning
confidence: 99%
“…30 Recently, several methods have been developed that may reveal regional glymphatic activity. [54][55][56] Therefore, the relationship between the DTI-ALPS index and glycemic clearance should be interpreted with caution. The sequential effect among glymphatic dysfunction, tau deposition, and clinical symptoms needs to be verified in longitudinal studies.…”
Section: Limitationsmentioning
confidence: 99%
“…There has been only one study that directly compared glymphatic activity measurement between the intrathecal contrast media administration method and the DTI-ALPS index method 30 . Recently, several methods have been developed that may reveal regional glymphatic activity 54–56 . Therefore, the relationship between the DTI-ALPS index and glycemic clearance should be interpreted with caution.…”
Section: Limitationsmentioning
confidence: 99%